Nilai Filosofis Bangunan Perpustakaan Ditinjau dari Pemikiran Arsitektur Posmodern - Iswanto, Rahmat; Hartati, Hasni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
This Article about the philosophical value of library buildings in terms of postmodern architectural thought is intended to answer the question of how important principles and values in a building are in the view of postmodern architectural experts, how the development of library buildings in Indonesia in particular. This paper is carried out by analyzing the philosophical values of postmodern architectural experts from various secondary sources. Important principles in preparing the building of a library can be adopted by digging information related to the science of architecture and experts. The expected benefits of this paper are important and aspirational information for research librarians and library workers to produce a further study related to the library building.